Lignocellulosic Waste Material – from Landfill to Sorbent and Fuel - R. Lopičić, Zorica; D. Stojanović, Mirjana; V. Milojković, Jelena; Lj. Kijevčanin, Mirjana (European Journal of Sustainable Development, 2017)
The most important source of renewable energy in Serbia represents biomass (60.3 %) with total potential of 3.405 million toe. Almost half of this amount (1.67 million toe) represents agricultural and industrial waste, with further negligible revalorization. Various investigations have demonstrated that agricultural byproducts have promising capacities to remove a variety of pollutants, which might increase the sustainability of their life cycle. This paper investigates the possible use of lignocellulosic waste material (LCW), originating from food industry as biosorbent for heavy metals, and later as a solid fuel. For this purpose we have used peach stone particles (PS) obtained by mechanical activation of this LCW as Cu(II) sorbent. The physical and chemical characteristics of PS reveal its complex structure which was confirmed by SEM, and FTIR analysis. PS behavior on pyrolysis process was studied by dynamic thermo gravimetric and derivate thermo gravimetric analysis. Results show that this lignocellulosic waste can be applied as sorbent and as a fuel. This approve that this agricultural waste can be a resource more than a waste and that it does not need to be disposed of in the costly and inefficient way, which is especially important in developing economies, like Serbian. Keywords: biomass, lignocellulosic waste, pollution prevention, sorption, fuel